Debonding‐On‐Demand Polymeric Wound Patches for Minimal Adhesion and Clinical Communication. Issue 29 (21st August 2022) - Zeng, Qiankun; Wang, Fangbing; Hu, Ruixuan; Ding, Xuyin; Lu, Yifan; Shi, Guoyue; Haick, Hossam; Zhang, Min
Abstract: Herein, a multifunctional bilayer wound patch is developed by integrating a debonding‐on‐demand polymeric tissue adhesive (DDPTA) with an ionic conducting elastomer (ICE). As a skin adhesive layer, the DDPTA is soft and adherent at skin temperature but hard and non‐tacky when cooled, so it provides unique temperature‐triggered quick adhesion and non‐forced detachment from the skin. During use, the dense surface of the DDPTA prevents blood infiltration and reduces unnecessary blood loss with gentle pressing. Moreover, its hydrophobic matrix helps to repel blood and prevents the formation of clots, thus precluding wound tearing during its removal. This unique feature enables the DDPTA to avoid the severe deficiencies of hydrophilic adhesives, providing a reliable solution for a wide range of secondary wound injuries. The DDPTA is versatile in that it can be covered with ICE to configure a DDPTA@ICE patch for initiating non‐verbal communication systems by the fingers, leading toward sign language recognition and a remote clinical alarm system. This multifunctional wound patch with debonding‐on‐demand can promote a new style of tissue sealant for convenient clinical communication. Abstract : In this work, a debonding‐on‐demand bilayer wound patch is introduced that can serve as a multifunctional platform for wound sealing and clinical communication with the wounded.